A Detailed Study on Diagnosis and Prediction of Diabetic Retinopathy Using Current Machine Learning and Deep Learning Techniques - Hemalatha, R.; Anjanadevi, V.; Naren, J.; Vithya, G. (International Journal of Psychosocial Rehabilitation, 2024)
Diabetic retinopathy is a disease that manifests itself in the retina of the human eye. The effects of the rudimentary stages of this disease include blurred vision, seeing dark spots due to accumulation of blood vessels, and later stages of this disease can cause complete blindness in 90% of cases. The detection and diagnosis of diabetic retinopathy is well established in the field of medicine and can be performed by professionals. The process is known to be expensive and cumbersome. However, the rise of machine learning and AI has paved the path towards disease detection, creating a niche for diabetic retinopathy. This paper reviews the current diabetic retinopathy detection literature and provides an insight into the various computer-aided methods of diabetic retinopathy detection.